Comparative Genomics of Clostridium perfringens Reveals Patterns of Host-Associated Phylogenetic Clades and Virulence Factors - Geier, Renae R.; Rehberger, Thomas G.; Smith, Alexandra H. (Frontiers in Microbiology, 2021)
Clostridium perfringens is a lethal opportunistic pathogenic bacterium that infects both animals and humans. C. perfringens genomes encode a diverse array of toxins and virulence proteins which continues to expand as more genomes are sequenced. In this study, the genomes of forty-four C. perfringens strains isolated from intestinal sections of diseased cattle and from broiler chickens from diseased and healthy flocks were sequenced. These newly assembled genomes were compared to 141 publicly available C. perfringens genome assemblies, by aligning known toxin and virulence protein sequences in the assemblies using BLASTp. The genes for alpha toxin, collagenase, a sialidase (nanH), and alpha-clostripain were present in at least 99% of assemblies analyzed. In contrast, beta toxin, epsilon toxin, iota toxin, and binary enterotoxin of toxinotypes B, C, D and E were present in less than 5% of assemblies analyzed. Additional sequence variants of beta2 toxin were detected, some of which were missing the leader or signal peptide sequences and therefore likely not secreted. The netB gene was only found in avian isolates, while netE, netF and netG were only present in canine and equine isolates. Alveolysin was positively associated with canine and equine strains and only present in a single monophyletic clade. Unlike avian, equine, and canine isolates that tended to be in monophyletic clades, ruminant isolates were present throughout the dendrogram and were not associated with particular virulence factors. A monophyletic clade containing C. perfringens associated with food poisoning lacked the genes for hyaluronidases and sialidases, important for attaching to and digesting complex carbohydrates found in animal tissues. Overall, the diversity of virulence factors in C. perfringens make these species capable of causing disease in a wide variety of hosts and niches.